Healing roots : anthropology in life and medicine - Laplante, Julie (New York: Berghahn, 2015)
"Umhlonyane, also known as Artemisia afra, is one of the oldest and best-documented indigenous medicines in South Africa. This bush, which grows wild throughout the sub-Saharan region, smells and tastes like "medicine," thus easily making its way into people's lives and becoming the choice of everyday healing for Xhosa healer-diviners and Rastafarian herbalists. This 'natural' remedy has recently sparked curiosity as scientists search for new molecules against a tuberculosis pandemic while hoping to recognize indigenous medicine. Laplante follows umhlonyane on its trails and trials of becoming a biopharmaceutical -- from the "open air" to controlled environments -- learning from the plant and from the people who use it with hopes in healing."--
Introduction: tracing the preclinical trial of an indigenous plant -- Knowing umhloyane/Artemisia afra -- Engaging in medicine -- Tracing medicine/wayfaring -- Imagining indigeneity -- Healing the nation -- Dreams, ancestors and sound healing -- Weaving molecules in life -- Conclusion--imagining the clinical trial.
Includes bibliographical references (pages 258-275) and index.
Keywords: Artemisia afra -- Therapeutic use -- South Africa; Medicinal plants -- South Africa; Traditional medicine -- South Africa; Medical anthropology -- South Africa; Ethnopharmacology -- South Africa; Molecular biology -- Social aspects; Drugs -- Testing; Tuberculosis -- Chemotherapy